Making Credibility Visible: How AI Influencer Credibility Builds Engagement, Loyalty, and Purchase Intention - Budi Setyanta; Mohamad Najmudin; Rakotoarisoa Maminirina Fenitra; Didik Setyawan; Luk Luk Atul Hidayati (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study examines how credibility attributed to AI-fronted influencers relates to consumer engagement, brand loyalty, and purchase intention in Indonesia's social-commerce setting. The goal is to analyse whether credibility moves intention directly or works mainly through relationship states. Research Design & Methods: A cross-sectional survey of Indonesian social-media users who recently encountered AI-influencer content was analyzed with PLS-SEM. Measurement quality met recommended thresholds, and predictive checks indicated practical, varied, out-of-sample relevance. Findings: Credibility strongly relates to consumer engagement. The direct credibility–intention link is not supported. Intention is explained indirectly—first via engagement and then via loyalty. Engagement positively associates with intention and loyalty; loyalty stands close to intention as the next step in choice. Implications & Recommendations: These findings extend Source Credibility Theory to AI influencers and streams by showing credibility drives purchase intention through engagement and loyalty. Brands should demonstrate expertise, keep a consistent tone, disclose AI or paid endorsement clearly, and show social proof early to spark interaction and return visits. Transparent disclosure supports informed choice and trust. Future research should test fit based moderated mediation with experiments or longitudinal data and AI human comparisons. Contribution & Value Added: The study integrates credibility, engagement, loyalty, and intention in one explanatory chain for an emerging market. It distinguishes a weak direct route from meaningful indirect routes and offers a practical blueprint for moving from attention to durable outcomes in AI-fronted campaigns.